Disinformation and Media: Thematic analysis of fact-check cases studies by international News Agencies - Boté-Vericad, Juan-José (Encontros da Licenciatura em Ciências e Tecnologias da Documentação e Informação, 2022)
News Agencies and fact-checking goals: • What do they fact-check ? • Which topics do the verify ? Methodology • Selection of 10 news per agency • No time time limit • Reuters News seems stopped on Feb-2020 • Content Analysis of their websites Conclusions • All of them analyse news differently and qualitative analysis seems better than other • There is no guidance on what do they check and publish • Télam educates is audiences through tools -> media literacy on site • DPA indicates that images are verified starting form reverse news • Future research → a more consistent datase